Pengaruh Model Realistic Mathematics Education (RME) terhadap Kemampuan Menyelesaikan Soal Cerita Perkalian Pecahan - Nur Fitriani; Moh. Romli; M. Zainal Arifin (Primer Edukasi Journal, 2022)
The purpose of this study: (1) with the exhibition media can improve the learning outcomes of Culture and Arts and Skills of the fifth grade students of SDN Gunung Picung 03; (2) the exhibition media can increase learning activities in the subjects of Culture and Arts and Skills of students in class V of SDN Gunung Picung 03; and (3) using exhibition media can play an important role in improving learning outcomes in the subjects of Art and Culture and Skills for fifth grade students at SDN Gunung Picung 03. The method used in this study is the Classroom Action Research (CAR) method. CAR is implemented as an effort to overcome problems that arise in the classroom. This method is carried out in four stages, namely planning, action, observation and reflection. The activity phase is a cycle that takes place repeatedly and is carried out with the same steps and is focused on learning Cultural Arts and Skills using exhibition media.. The results showed that the results of the study of the subjects of Culture and Art by using exhibition media had increased. These improvements are: (1) Student learning outcomes increased by 4.52%; (2) The percentage of study completion increased by 13.51%; and (3) the percentage of student learning activities increased by 23.07%.. So that the students will be more maximized due to the development of the right and left brain functioning and developing better and balanced. Based on the results of this study, it can be concluded that using exhibition media can improve student learning outcomes, student learning activities, and the role of art and culture subjects in class V of SDN Gunung Picung 03. Keywords: Learning Outcomes, Cultural Arts and Skills, Exhibition Media